STAGES, FORMS, AND METHODS OF IMPROVING THE METHODOLOGY FOR DEVELOPING STUDENTS’ WRITING SKILLS - Muydinov Mansurjon Ilhomhon o‘g‘li, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
ANNOTATION: This article investigates the stages, forms, and methods that contribute to the enhancement of methodologies for developing students’ writing skills. Writing is considered a fundamental component of foreign language education and a vital factor in academic success. The study emphasizes that the improvement of writing competence  requires  a  structured  methodological  framework  combining  theoretical principles,  practical  application,  and  innovative  teaching  strategies.  It  identifies essential stages of writing development, explores pedagogical forms of teaching, and examines effective techniques for fostering students’ written proficiency in educational contexts.